Aplikasi Health Belief Model Pada Penanganan Kegawatdaruratan Anak Dengan Kejang Demam Di Rumah - Tri Widyastuti Handayani; Dyah Dwi Astuti; Duwi Pudji Astuti (Poltekkes Kemenkes Surakarta, 2021)
Background: A febrile seizure have negative impacts for children and parents if mismanagement. A febrile seizure in children of disorder causing fear of cognitive development and achievement in their school as increase the risk of attention deficit hyperactifity disorder (ADHD). The purpose of this community service activity is to improve knowledge and skills on the emergency management of fever-convulsed children at home with the Health Belief Model approach. Methods: Community service activities are conducted through education and small group discussions are created by facilitators. Results: The result of this community service activities showed the increased the value of test weighted pre (65) and post (80). Increased knowledge parents as first responder in children with febrile seizure are needed to increade the ability home emergency first aid for children having a febrile seizure. Conclusion: Community service activities was applied the evidence based practice of health belief model in home emergency first aid for children having a febrile seizure.